Cover Picture: The Ligand‐Based Quintuple Bond‐Shortening Concept and Some of Its Limitations (Chem. Eur. J. 30/2013). Issue 30 (15th July 2013) - Noor, Awal; Bauer, Tobias; Todorova, Tanya K.; Weber, Birgit; Gagliardi, Laura; Kempe, Rhett
<x xml:space="preserve">Abstract</x> Quintuple bonds between chromium atoms are the first choice for looking at how short a metal–metal bond can be. In their Full Paper on page 9825 ff., L. Gagliardi, R. Kempe et al. describe a rational concept of shortening quintuple bonds based on ligand design. A Cr–Cr distance of 1.7056(12) Å is the value finally reached. Most importantly, the potential limitations of the shortening concept and the formation of other coordination isomers or over‐reduction are described.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>